Analisa Pengaruh Human Error Terhadap Kecelakaa Kerja Di PT. Industri Kapal Indonesia Dengan Menggunakan Pendekatan Cross Sectional Method - Jaiyen Pagau; Pahrizah Puji Anugrah (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2021)
One of the critical processes in offshore fabrication is the transfer of the offshore module (Top Side) from the top of the jetty to PT. The Indonesian Ship Industry is a company that is engaged in shipbuilding and ship repair. This company has implemented an environmental management system, occupational safety, and health. There is a relationship between human factors and work accidents. Therefore we need a study that aims to identify the human factors that cause work accidents, study the characteristics of human factors on respondents to work accidents, and analyze the influence of human factors on accidents. This study will apply a questionnaire method of 30 respondents to collect primary data from several respondents and is a cross-sectional study. The results showed that 15 (50%) workers had minor injuries, 3 (10%) workers had serious accidents, and 12 (40%) workers had never been injured. It is expected that the company will provide sufficient information to workers about the importance of OHS, be more intensive in providing training programs, hold safety contests by providing rewards for workers and that workers will be able to increase discipline in the use of personal protective equipment and increase awareness to create a work environment safety.